Embedded aluminum sections and prestressed high-performance concretes for improving shear performance of RC beams - Galal Elsamak; Mohamed Ghalla; Jong Wan Hu; Abdullah Albogami; Mohamed Emara; Shiren Osman Ahmed (Case Studies in Construction Materials)
The paper presents a novel sustainable technique for shear strengthening of reinforced concrete (RC) beams utilizing embedded aluminum boxes and prestressed high-performance concretes (HPCs). It addresses the challenges faced by existing RC structures, such as environmental threats, increased loading, and aging, which often lead to shear reinforcement deficiencies. Through an experimental program, the paper evaluates the impact of several parameters on the shear performance of beams, including the type of concrete filling the aluminum boxes, the type and diameter of reinforcement, and the level of prestressing force. The findings demonstrate the potential of this innovative technique to enhance the shear behavior of damaged RC beams, contributing to more sustainable construction practices. Results revealed that increasing the bar diameter provided marginal additional benefits. Moreover, the use of glass fiber reinforced polymer (GFRP) bars offered superior strengthening compared to steel bars. Additionally, beams strengthened with ultra-high-performance concrete (UHPC)-filled aluminum boxes and embedded steel/GFRP bars, demonstrated improved performance compared to strain-hardening cementitious composites (SHCC)-filled aluminum boxes. Applying a prestressing force significantly enhanced the behavior of strengthened beams, the ultimate capacity of one of them reaching that of the control beam. The level of enhancement directly correlated with the applied prestressing force. This research successfully validated a new finite element model (FEM) for analyzing concrete beams strengthened with aluminum boxes. The model accurately predicted shear strength of these beams. Additionally, a proposed formula for calculating shear capacity closely matched experimental results, showing a maximum discrepancy of only 2.5 %.